2008
DOI: 10.1002/ejoc.200800222
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of Intramolecular Aldol Reactions of Dialdehydes

Abstract: Transition states associated with the C-C bond-formation step in proline-catalyzed intramolecular aldol reactions of 1,7-dialdehydes were studied using density functional theory methods (DFT), at the B3LYP/6-31G(d,p) level. A polarizable continuum model (PCM) was used to describe solvent effects. Two reactive channels, corresponding to the anhydrous system or to the explicit inclusion of water have been analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 50 publications
4
20
0
Order By: Relevance
“…The transition‐state structures shown in Figure 3 for the proline‐catalyzed cyclization of hept‐2‐enedial ( 1 ) are, in many aspects, similar to the model recently proposed by us22b and List and co‐workers4d for the cyclization of heptanedial. The differences arise from the γ,δ‐double bond, which was absent in the aldol cyclization of List and co‐workers.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The transition‐state structures shown in Figure 3 for the proline‐catalyzed cyclization of hept‐2‐enedial ( 1 ) are, in many aspects, similar to the model recently proposed by us22b and List and co‐workers4d for the cyclization of heptanedial. The differences arise from the γ,δ‐double bond, which was absent in the aldol cyclization of List and co‐workers.…”
Section: Resultssupporting
confidence: 76%
“…It is known that the main driving force for the cyclization step is the stabilization of the negative charge on the forming alkoxide group 22b. 24 This means that any attractive electrostatic contact with the O1 atom will contribute to the stabilization of the transition state.…”
Section: Resultsmentioning
confidence: 99%
“…Two mechanistic proposals can be found in the literature. Although many theoretical studies of aldol reactions have been reported in the literature, [55][56][57][58][59][60][61][62][63][64][65][66] only few studies are focused on the Lewis-acid catalyzed Mukaiyama aldol reactions. The first step is the carbon-carbon bond formation.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of the proline catalyzed aldol reaction has been studied by Boyd,2 Houk,3 and other groups 4. The reaction takes place through an enamine intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…In that model, hydrogen bonding and the geometry for proton transfer play important roles and determine the stereoselectivity of the reaction. Catalysis of the aldol reaction by proline analogs, including bicyclic prolines,5 heteroatom-substituted prolines,4c prolinamides,6 prolinol ethers7, and amine-, ammonium-, and tetrazole-functionalized pyrrolidines8 (Figure 1), have also been studied computationally. Computational investigations of the Mannich,9 Michael addition,6e, 7b, 10 and Morita-Baylis Hillman11 reactions by proline catalysts have also been reported.…”
Section: Introductionmentioning
confidence: 99%